Frequency of Hypocalcemia in Breast Fed Infants Presenting with Afebrile Fits - Rabbia Shaheen, Bakht Muhammad, Tahira Nargis, Sadia Jehanzeb, Khalida, Shahidullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The goal of this study is to assess the prevalence of hypocalcaemia in breast-fed babies who present with afebrile fits. Methods: After the ethical approval from the institutional review board, this cross-sectional study was carried out at Paediatric Department, Hayatabad Medical Complex Hospital, Peshawar, from August, 2019 to January, 2020. Inclusion and exclusion criteria were strictly followed in order to avoid confounding variables and bias in study. Information regarding age, gender, weight, types of fits and calcium level of child and mother were recorded in a pre-designed Performa. Collected data were then entered into the computer for further analysis using SPSS (version 20). Results: Results showed that out of total subjects 59.7% were male and 40.3% were females. Mean age was 3.81±1.55 months while 60% were in the age group of 4-6. Mean weight and length was 2.20 ±1.24 kg and cm respectively. Weight for age (WFA) of 64.5% had less than 5th percentile. Mean serum calcium of infant and mothers are 6.98±1.83 and 8.02±1.26 respectively. 62.7% of cases were hypocalcemia while 37.3% had normal calcium level. 33.1% of subjects had generalized tonic clonic fits and 15.8% had focal fits. A significant (p<0.05) association was found among prevalence of hypocalcemia in male gender and in the age group of 46 months respectively. Hypocalcemia was non-significantly (p>0.05) associated with types of fits (generalized tonic clonic, tonic, clonic and focal). Conclusion: The results of the current investigation indicated that both nursing babies and their mothers had a significant incidence of hypocalcemia. Breastfeeding moms are encouraged to soak up some rays themselves, and should also make sure their babies do the same. Calcium and vitamin D supplementation in nursing moms and their infants: a systematic review and meta-analysis. Hypocalcemia is quite common in pregnant women, and its causes need to be investigated more. Keywords: hypocalcemia, breastfeeding, seizures